Novel Results for the κ–μ Extreme Fading Distribution: Generation of White Samples and Capacity Analysis - López-Martínez, Francisco Javier; Moreno-Pozas, Laureano; Martos-Naya, Eduardo (IEEE Communications Letters, 2015)
We provide new analytical results for the κ-μ extreme (κ-μ-E) fading distribution, which is useful to model propagation conditions more severe than Rayleigh fading. First, we calculate a closed-form expression for the cumulative distribution function in terms of the first-order Marcum Q-function, which allows us to accurately generate κ-μ-E distributed random variables using the inversion method. Then, we investigate the ergodic capacity in this scenario. Strikingly, we observe that the capacity in the high-SNR regime scales differently than in all conventional fading models.
Keywords: Sistemas de comunicaciones inalámbricos; Rayleigh channels; Mathematical model; Channel capacity; Signal to noise ratio; Wireless communication